Analisis Faktor-Faktor Yang Memengaruhi Loyalitas Konsumen Tupperware (Studi Pada Konsumen Tupperware di Universitas Diponegoro) - Nurullaili Nurullaili; Andi Wijayanto (Universitas Diponegoro, 2013)
This research aims to analyze the factors affecting loyalty of Tupperware customers. Estimated factors that affect customer loyalty are product quality, price, promotion, and design variables. This research is an explanatory research. Sampling technique is a purposive sampling, with a sample of 100 Tupperware customers at Diponegoro University. The analysis method used in this research is a multiple linear regression analysis. The result of this study indicates that product quality, price, promotion, and design variables are factors that significantly affect customer loyalty. Price variable is the most influential factor to customer loyalty. The coefficient of determination of 0.854 indicates that 85.4 percent of variation in customer loyalty can be explained by four independent variables used in the regression equation. This research suggests Tupperware keep the quality of its products and enchance promotion. The product design should be more interesting to make people more loyal to this product.